1977
DOI: 10.1126/science.198877
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension: Increase of Collagen Biosynthesis in Arteries but Not in Veins

Abstract: In two models of hypertension in rats, it was shown that collagen synthesis and deposition are increased in arteries where blood pressure is elevated. By contrast, there were no alterations in any of the markers of collagen synthesis in veins, where blood pressure was only slightly elevated. It would appear that the stimulus for vascular collagen synthesis is provided by a direct effect of the increased pressure on the arterial cells rather than by a humoral factor released into the general circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 14 publications
1
17
1
2
Order By: Relevance
“…Hypertension may be considered another type of insult or injury, analogous to the above examples, which impinges on the entire vascular bed exposed to the increased pressure (2). In support of this localization of response, we have recently found that veins of hypertensive animals, which are not exposed to increased pressure, do not show increased collagen synthesis (26).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Hypertension may be considered another type of insult or injury, analogous to the above examples, which impinges on the entire vascular bed exposed to the increased pressure (2). In support of this localization of response, we have recently found that veins of hypertensive animals, which are not exposed to increased pressure, do not show increased collagen synthesis (26).…”
Section: Discussionmentioning
confidence: 50%
“…In one set of experiments, treatment of hypertensive rats with f-aminopropionitrile, an inhibitor of collagen crosslinking, resulted in a lowering of the blood pressure within 3 weeks (3). If collagen deposition itself leads to a maintenance of the elevated pressure as we have proposed (3), then this reversal in such a short time may indicate that in hypertension collagen breakdown as well as synthesis may be accelerated. To investigate this possibility, we set about to measure the decay in specific activity of protein-bound hydroxyproline (collagen) after rats were labeled with L- [2,3-3H]proline.…”
mentioning
confidence: 99%
“…IFN-y not only decreased the basal synthesis of collagen by VSMCs but also blocked the augmentation in collagen biosynthesis produced by PDGF and TGF-0 (Figures 3 and 4). This inhibitory effect of IFN-y on collagen synthesis by VSMCs was quite selective, as the lymphokine did not alter incorporation of 35 S-methionine into overall cell proteins (data not shown). IFN-y also selectively alters expression of other genes in VSMCs.…”
Section: Resultsmentioning
confidence: 95%
“…Matrix also accumulates in hypertensive arteries, probably due in part to increased collagen synthesis. 35 For these reasons, the capacity of VSMCs to synthesize extracellular matrix constituents has interested investigators since the introduction of modern culture techniques for this cell type. 2336 Burke et al 5 and Burke and Ross 37 found that exposure to platelet products increased collagen synthesis by primate arterial VSMCs.…”
Section: Resultsmentioning
confidence: 99%
“…"• 174 In SHR, there is evidence for increases in venous wall mucopolysaccharides and glycoprotein, 171 as well as smooth muscle hypertrophy. 171 ' 17S Venous wall collagen content may be normal 172 or decreased. 17 * Rats with twokidney, one clip hypertension apparently do not develop muscle hypertrophy in portal vein, 178 but onekidney, one clip rats may.…”
Section: Wall Compositionmentioning
confidence: 99%